2012
DOI: 10.1155/2013/126106
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Iran′s Pistacia atlantica Cold‐Pressed Oil

Abstract: The lipid fraction ofPistacia atlanticaseeds was extracted for the first time by means of cold-press technique and analyzed for its chemical composition. The fatty acids, sterols, triacylglycerols (TAG), tocopherols, polyphenols, and pigments were identified and their concentrations were determined by means of reversed-phase high-performance liquid chromatography (RP-HPLC) and gas chromatography (GC). Because of its high content of unsaturated fatty acids, it might prove to be of value in diets and it may be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
2
30
1
Order By: Relevance
“…These results were in accordance with previous studies reported by Durmaz and Gokmen , which are generally attributed to the thermal degradation or microstructural changes in kernels during roasting. Chlorophylls are usually associated with color and quality of some plant oils, and RPKO contains relatively high level of chlorophylls (12.21 mg/kg oil), which is similar to the values reported by Saber‐Tehrani et al for cold‐pressed pistachio kernel oil from Iran (17.21 mg/kg oil). After roasting chlorophylls levels were reduced slightly (9.95–10.23 mg/kg oil).…”
Section: Resultssupporting
confidence: 87%
“…These results were in accordance with previous studies reported by Durmaz and Gokmen , which are generally attributed to the thermal degradation or microstructural changes in kernels during roasting. Chlorophylls are usually associated with color and quality of some plant oils, and RPKO contains relatively high level of chlorophylls (12.21 mg/kg oil), which is similar to the values reported by Saber‐Tehrani et al for cold‐pressed pistachio kernel oil from Iran (17.21 mg/kg oil). After roasting chlorophylls levels were reduced slightly (9.95–10.23 mg/kg oil).…”
Section: Resultssupporting
confidence: 87%
“…To our knowledge, this is the first time that the variation of phenolic compounds in P. atlantica fruits oil has been studied and substantial amounts of phenolic compounds in the unripe fruits oil have been reported. Saber‐Tehrani et al () noted that caffeic acid and cinnamic acid were the predominant phenolic compounds in P. atlantica cold‐pressed oil (1.96 mg kg −1 oil and 0.67 mg kg −1 oil respectively). As shown in Table , our unripe fruits oil contains a high level of phenolic compounds that were dominated by flavonoids (65.33%).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first time that all tocopherols of P. atlantica fruit oil have been analyzed on a polar silica column, which allows for a good separation not only for the four isomers but also the corresponding tocotrienols ( Figure 1). It seems that there is a difference between the studied groups concerning tocotrienol isomers, but a study of tocotrienol composition is necessary to confirm these observations Saber-Tehrani et al studied the tocopherol composition of Iranian P. atlantica cold pressed oil using a C-18 Lichrospher RP-100 apolar column and they reported that α-tocopherol was largely the most predominant [16]. Ours results on P. atlantica seem to be similar to those of Matthäus and Özcan for P. terebinthus [17].…”
mentioning
confidence: 99%